2022
DOI: 10.1177/01614681221086115
|View full text |Cite
|
Sign up to set email alerts
|

Connection, Antiblackness, and Positive Relationships That (Re)Humanize Black Boys’ Experience of School

Abstract: Background/Context: Black people continue to be popularly imagined as lacking humanity and, as such, are often the disproportionate subjects of unceasing race-gender terror and state violence. A vast body of scholarship has documented the failure of schools to adequately serve Black youth in general, and Black boys and men in particular. There is compelling evidence, however, that consistently humanizing interactions with adults in school lead to positive relationships that in turn may protect against Black bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Interactions between police or School Resource Officers (hereafter SROs) and Black youth often reveal the manifestations of antiblackness. For example, antiblackness renders Black children as threatening or suspicious regardless of what their bodies are physically doing (Coles & Powell, 2020;Jenkins, 2022;Jenkins, 2023b;Morris, 2016;Warren and Coles, 2020;Warren et al, 2022); in need of constant oversight and supervision (Browne, 2015;Okello, 2022). Such perspectives underlie the institutional foundations of contemporary policing in the United States as evidenced by early manifestations of law enforcement in southern states like Louisiana, Georgia, and South Carolina where uniformed officers were empowered to monitor and enforce discipline upon the enslaved (Muhammad, 2019).…”
Section: Antiblackness Law Enforcement and The Project Of American Sc...mentioning
confidence: 99%
“…Interactions between police or School Resource Officers (hereafter SROs) and Black youth often reveal the manifestations of antiblackness. For example, antiblackness renders Black children as threatening or suspicious regardless of what their bodies are physically doing (Coles & Powell, 2020;Jenkins, 2022;Jenkins, 2023b;Morris, 2016;Warren and Coles, 2020;Warren et al, 2022); in need of constant oversight and supervision (Browne, 2015;Okello, 2022). Such perspectives underlie the institutional foundations of contemporary policing in the United States as evidenced by early manifestations of law enforcement in southern states like Louisiana, Georgia, and South Carolina where uniformed officers were empowered to monitor and enforce discipline upon the enslaved (Muhammad, 2019).…”
Section: Antiblackness Law Enforcement and The Project Of American Sc...mentioning
confidence: 99%
“…This means viewing racialized and gendered experiences of identity as coconstructed and inseparable (Rogers et al, 2015). Through conversations with 28 Black boys across the K-12 years, Warren et al (2022) found that ongoing positive interpersonal interactions and connections can counter pervasive anti-Black stereotypes as a form of structural intervention to surveillance. They detail how one student emphasized the nuanced qualities of "interaction with adults that consistently suggest to Black boys they are inherently good, which in turn generally puts them in a better position to learn" (Warren et al, 2022, p. 125).…”
Section: Moving With Women Of Color Feminist and Abolitionist Approachesmentioning
confidence: 99%
“…Writing (for) the self is precarious “because one’s writing is closely tied to one’s thinking and being, and situated in a world that readily nourishes the being and becoming of some over others” (Vossoughi et al, 2021, p. 203). In a world that has historically dehumanized and oppressed Black, Indigenous, and other People of Color (BIPOC), schooling has been a central mechanism for “settler colonial logics and hegemonic norms” (Eagle Shield et al, 2021, p. 39) that perpetuate entrenched inequities and render BIPOC voices illegible/invisible (Warren et al, 2022). Any accounting of youth writing must consider how young people navigate these “historically powered relations” that make it challenging to inscribe oneself into existence in systems and institutions that have silenced or co-opted nondominant perspectives and privileged the humanity of some over others (Bang & Vossoughi, 2016, p. 184).…”
Section: Writing As Praxis: Youth Agency and Writing (For) The Selfmentioning
confidence: 99%